Técnica exegética y su incidencia en el rendimiento escolar de los estudiantes de sexto año de básica de la Escuela Aurora Estrada y Ayala de Ramírez Pérez, de la ciudad de Babahoyo, Provincia de Los Ríos, durante el periodo 2017 - Leyton Moran, Karina Anabel (2017)
This work was developed in order to seek to satisfy the knowledge and learning of the exegetical technique in the teaching-learning process in students of the sixth year of basic education of the School of Basic Education "Aurora estrada y Ayala de Ramírez Pérez", through developed in class and the permanent search for improvement in the quality of learning by studying individual, group and mixed teaching methods The application of this technique requires the consultation of works by authors, treatises or, at least, compendia containing selected sections of different authors, on the subject studied. This technique can also be called commented reading. It tends to apprehend, with precision, what a text intends to communicate and which is often concealed by the difficulty of interpretation or between the lines of it. In short, it consists of the commented reading of texts related to the subject under study, it requires consulting works by authors and getting used to reading the representative works of an author, a topic or a discipline. The importance of what has been read needs to be highlighted, a significant piece can also be indicated for each student to study, analyze and interpret, explaining, in turn, words, phrases or doubtful pieces. You can interpret the text and the relationships that have influenced the author.